Self-compassion in chronic pain: Validating the self-compassion scale short-form and exploring initial relationships with pain outcomes - Rakhimov, A. (BRITISH JOURNAL OF PAIN, 2025)
Objectives: Validate the English version of the Self-Compassion Scale Short-Form (SCS-SF) as a reliable measure in chronic pain. Explore self-compassion's relationship with pain-related outcomes. Methods: A total of 240 chronic pain patients (at 6-months) and 256 community participants (at 12-months) completed two prospective survey studies. SCS-SF psychometric properties were evaluated through exploratory and confirmatory factor analyses (EFA and CFA), exploratory structural equation modelling (ESEM), test-retest reliability (Pearson's r) and internal consistency (Cronbach's alpha) in both samples. Convergent validity/clinical relevance was assessed in the chronic pain sample via univariate linear regressions between self-compassion and pain intensity, interference, catastrophizing, self-efficacy, anxiety and depression. Results: The SCS-SF showed acceptable internal consistency in both samples (alpha > 0.70, range = 0.74-0.79), high test-retest reliability over 6-months in the pain sample (r = 0.81, p < .001) and sub-threshold over 12-months in the community (r = 0.59 p < .001). EFA revealed a two-factor model distinguishing compassionate and uncompassionate self-responding in both samples. CFA identified a one-factor and two-factor model in both samples, but it did not meet statistical thresholds. ESEM identified the best fit for the chronic pain group was for a two-factor model (RMSEA and SRMR < 0.08; CFI and TLI > 0.90), whereas no models met acceptable fit criteria in the community group. A two-bifactor Bayesian model had suitable fit in both groups. In the chronic pain sample, SCS-SF and compassionate self-responding negatively predicted pain intensity, interference, anxiety, depression, catastrophizing and positively predicted self-efficacy over 6-months. Uncompassionate self-responding positively predicted anxiety, depression, catastrophizing and negatively predicted self-efficacy but did not predict pain outcomes. Discussion: The SCS-SF is a reliable and valid measure in chronic pain. Total and sub-factor scores appear to have distinct relationships with pain outcomes. Future research should consider self-compassion as a unitary and/or bifactorial (consisting of compassionate and uncompassionate self-responding) construct in chronic pain when measured using the SCS-SF.
Keywords: Chronic pain, self-compassion, psychometrics, exploratory structural equation modelling, factor analyse